Efektivitas Manajemen Haji dan Umrah dalam Meningkatkan Kepuasan Jamaah di Indonesia: Sebuah Studi Literatur - Chulaivi, Ahmad; Khazimi, Ibrahim Zaky; Ikram, Muhamad; Hafiz, Abdul (LANCAH: Jurnal Inovasi dan Tren, 2024)
The effectiveness of Hajj and Umrah management is a crucial factor in enhancing pilgrims' satisfaction in Indonesia. This study evaluates various aspects of Hajj and Umrah management, including the use of technology, service quality, and logistics management. The findings indicate that technological innovations such as mobile applications and the Integrated Hajj Computerization System (SISKOHAT) significantly improve efficiency and pilgrim satisfaction. Furthermore, adequate accommodation, transportation, and healthcare services greatly influence pilgrim satisfaction. Key recommendations include strengthening information technology infrastructure, human resource training, improving facility quality, and providing comprehensive religious guidance. By adopting more effective management approaches, it is expected that the Hajj and Umrah experience for Indonesian pilgrims can be further enhanced.